2001
DOI: 10.1111/j.1523-5394.2001.96007.pp.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Sequelae and Alopecia Among Women with Cancer

Abstract: PURPOSE: This article reviews the relevant literature on treatmentinduced alopecia in women with cancer and describes the development of a computer-assisted intervention to reduce distress associated with this side effect. DESCRIPTION OF PROGRAM:Alopecia has been cited as the most disturbing anticipated side effect by up to 58% of women preparing for chemotherapy, with 8% being at risk for avoiding treatment. Women with cancer who experience alopecia as a side effect, compared with women with cancer and no alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 46 publications
0
55
0
3
Order By: Relevance
“…The relatively low rate of alopecia with carboplatin/patupilone is an important advantage to this combination, particularly in the treatment of women. Alopecia has been cited as the most disturbing side effect anticipated by almost 60% of women preparing for chemotherapy and is a risk factor for the discontinuation of therapy (28). Treatment-related neuropathy, a significant side effect of the taxanes, was uncommon.…”
Section: Resultsmentioning
confidence: 99%
“…The relatively low rate of alopecia with carboplatin/patupilone is an important advantage to this combination, particularly in the treatment of women. Alopecia has been cited as the most disturbing side effect anticipated by almost 60% of women preparing for chemotherapy and is a risk factor for the discontinuation of therapy (28). Treatment-related neuropathy, a significant side effect of the taxanes, was uncommon.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the results reported in individual clinical trials. Although not necessarily life threatening, neuropathy can be dose limiting and functionally debilitating [31], and alopecia can have a significant impact on a patient's psychological wellbeing [32,33]. These side effects are important to consider when choosing therapeutic strategies.…”
Section: C؉pldmentioning
confidence: 99%
“…12,13 In one study, 8% women were found to be at risk of avoiding treatment secondary to fear of baldness. 14 Irreversible/permanent alopecia has been described but its exact incidence remains unknown 4-9 and its mechanism is not well studied. It is mostly reported after high-dose Bucontaining regimens.…”
Section: Discussionmentioning
confidence: 99%